Corporate Social Responsibility Dalam Perpektif Islam - Mufti Afif (University of Darussalam Gontor, 2017)
This research is comparison study between convetional concept of CSR and Islamic concept. These two concepts, they are fundamental distinction, such in philosophy aspect and objective aspects. Conventional CSR generally on solving problem of poverty in addition to obtain the level of profit such as the trust of society. Whereas CSR responsibilities related to Islam between individual and social responsibilities of humanity. On basic of philosophy of CSR aspects of Islam in Quran and Sunnah, which deliver on the concept of relationship between institution and society or environment. This means the bond is stronger than conventional concept of CSR, which are only binding based on public confidence at Islamic Institution teaches that worship is not limited on the worship of mahdhah (hablumminallah), but other worship mahdhah also so due to considerations related to social worship (hablumminannas); This cue contained in God’s Word QS. Al-Ma’un verses 1-7. Islam has the principle of accountability which is balanced in all shapes and spaces in scope. Between body and soul, between individuals and between individuals and the family, social and, between a community with other societys and finally CSR Islam far has nailai maslahah compared to conventional CSR.